Alcohol consumption and its correlation with medical conditions: a UK Biobank study - Mayer, Craig S.; Fontelo, Paul (Frontiers in Public Health, 2024)
Alcohol consumption has been associated with the occurrence of many health conditions. We analyzed UK Biobank data to explore associations of various conditions to type and amount of alcohol consumed. UK Biobank is a large biomedical database providing information from UK participants, including lifestyle questionnaires and diagnosis data. Using UK Biobank, we examined the relationship between weekly alcohol consumption, alcohol type and the incidence of eight select conditions. We calculated counts of individuals consuming each type diagnosed with these conditions. To assess the effect of alcohol consumption on each condition’s prevalence, we used log-logistic regression models to generate dose-response models for each alcohol type. The alcohol consumed included: red wine (228439 participants), white wine (188811), beer (182648), spirits (129418), and fortified wine (34598). We observed increased condition prevalence with increasing amounts of alcohol. This was especially seen for chronic obstructive lung disease, cirrhosis of liver, hypertension, gastritis, and type 2 diabetes. Beer consumers showed higher prevalence for most conditions while fortified wine had the largest increases in incidence rates. Only white wine showed decreased incidence for acute myocardial infarction. In general, the prevalence of many conditions was higher among alcohol consumers, particularly for hypertension, 33.8%, compared to 28.6% for non-drinkers. Although many conditions were already prevalent among non-drinkers, participants consuming increasing amounts of alcohol had increased incidence rates for many of the studied conditions. This was especially true for consumers of beer and fortified wine, but also true to a lesser extent for consumers of spirits, red and white wine.